2018
DOI: 10.3390/s18072221
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Response of Jointed Rock Masses Inferred from Infrared Thermographic Surveying (Acuto Test-Site, Italy)

Abstract: The Mediterranean region is affected by considerable daily and seasonal temperature variations due to intense solar radiation. In mid-seasons, thermal excursions can exceed tens of degrees thus influencing the long-term behaviour of jointed rock masses acting as a preparatory factor for rock slope instabilities. In order to evaluate the thermal response of a densely jointed rock-block, monitoring has been in operation since 2016 by direct and remote sensing techniques in an abandoned quarry in Acuto (central I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 63 publications
5
32
0
Order By: Relevance
“…Reference [14] resume an interesting application, such as the study of heat capacity of rocky walls and monitoring of waste disposal sites. Moreover, some authors [15][16][17] used IRT to characterize the thermal response of rocks and joints, as well as landslide mapping [18][19][20][21]. On the other hand, TC measurement techniques are usually applied in engineering to test buildings materials, such as concrete and insulations [22], in the electronics industry [23], in developing new materials (e.g., nanomaterials and polymers, [24]), and for fire prevention [25].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [14] resume an interesting application, such as the study of heat capacity of rocky walls and monitoring of waste disposal sites. Moreover, some authors [15][16][17] used IRT to characterize the thermal response of rocks and joints, as well as landslide mapping [18][19][20][21]. On the other hand, TC measurement techniques are usually applied in engineering to test buildings materials, such as concrete and insulations [22], in the electronics industry [23], in developing new materials (e.g., nanomaterials and polymers, [24]), and for fire prevention [25].…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6). Given the sudden temperature decrease, it is possible to assume that the snowfalls were associated with the favoured cooling and subsequent freezing of the water-permeated joints, at least in the external thermal active layer (i.e., the first 8 cm from the surface; Fiorucci et al 2018;Marmoni et al 2020), as demonstrated by the negative temperature values recorded by the thermometer within the rock mass. However, no instrumental constraints on the wetness conditions of joints are available to date.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this permanent monitoring system, an array of seismic sensors was temporarily installed before the expected drop in temperature related to the incoming intense meteorological event. On 23 February 2018, 6 Bruel & Kjaer one-component accelerometers (type 8344: frequency range 0.2-3000 Hz, sensitivity 250 mV/ms −2 ) were deployed on the sides of the protruding monitored rock block, spaced 15-20 cm apart along a horizontal alignment across major-and micro-joints over a space corresponding to the daily thermal active layer (Fiorucci et al 2018;Marmoni et al 2020). These sensors were tightened to studs previously fixed within the rock mass to ensure the best coupling with the rock mass matrix.…”
Section: The Multi-parametric Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [ 14 ], along the Italian mountain ranges (Alps and Apennines), fast moving landslides such as rockfalls caused the largest number of deaths. As demonstrated in recent studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], surveying and monitoring activities play a key role in rockfall hazard assessment and are therefore of paramount importance for the preservation of human life. As rockfalls occur in very steep slopes sometimes showing limited precursor signals [ 24 , 25 , 26 , 27 , 28 , 29 ], their investigations, as well as their prediction and stabilisation, could face many difficulties [ 30 ].…”
Section: Introductionmentioning
confidence: 99%